PENGARUH DER, DAR DAN SIZE TERHADAP ROA PADA PERUSAHAAN KONSTRUKSI - saprudin, saprudin; Sulthoni, Abdilah Umar; Dewi, Sita; Hadi, Sofyan (Relevan : Jurnal Riset Akuntansi, 2025)
This study aims to determine and analyze the Effect of Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), and Company Size (SIZE) on Return on Asset (ROA) in Construction Companies listed on IDX in 2018-2022. This study is quantitative and is compiled based on data from 12 company samples, which were taken using the purposive sampling method. The analysis used multiple linear regression, simultaneous tests, and partial tests. From the results of the data processing carried out, it was concluded that DER had a negative and significant effect on ROA, DAR had a positive but not significant effect on ROA, SIZE had a negative and significant effect on ROA, and simultaneously DER, DAR, and SIZE had a significant effect on ROA. These variables have an influence value of 27% on ROA, with the other 73% influenced by other variables.